The Decline of Transmart: How Brand Image, Price, and Lifestyle Affect Consumer Satisfaction and Purchasing Decision - Aloysius Rangga Aditya Nalendra; Slamet Heri Winarno; Agus Priadi (University of Merdeka Malang, 2024)
This study is of the quantitative causative kind, meaning that it searches for causal links resulting. The sampling technique used by researchers is a convenience sampling technique where the subject is chosen because of the ease of access and location of the respondent with the researcher while the object under study is one of the closed Transmart branches located at ITC Cempaka Mas. The sample size was 150 people. This study investigates the problem of the closure of numerous Transmart stores. This study hypothesizes that factors such as brand image, pricing, and lifestyle affect consumer satisfaction and purchase decisions. The study's conclusions indicate that all of the hypotheses put forth are true, and every variable shown to have a substantial impact on the dependent variable is also accepted.